Characterizing Variation in Nursery Pig Growth Performance Based on Different Allotment Strategies - Jenna J. Bromm; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 360 pigs (200 × 400, DNA; initially 13.8 ± 1.83 lb BW) were used in a 42-d nursery trial to evaluate multiple procedures to allot pigs to pens and pens to treatment in swine nursery research. At placement, pigs were randomly assigned to 1 of 3 different allotment strategies. For the first strategy (random), pigs were allotted to pens using a completely randomized design. For strategy 2 (body weight distribution), pigs were sorted by body weight into 1 of 5 groups. Pigs were then randomly assigned to pen so there was 1 pig from each weight group in each pen to ensure that distribution of body weights within pen was relatively consistent across pens. For strategy 3 (body weight group), pigs were sorted by body weight to create 3 body weight categories: light, medium, and heavy. Within each group, pigs were randomized to pen such that each pen consisted of pigs from a single body weight group (pens of light pigs, pens of medium pigs, pens of heavy pigs). There were 72 pens on test with 5 pigs per pen and 24 pens per allotment strategy. For all allotment strategies, once pigs were allotted to pens, pens were allotted to 1 of 2 environmental enrichment treatments for a concurrent trial. There were no allotment × enrichment treatment interactions (P>0.10), so only effects of allotment strategy will be described herein. There were no statistical differences in ADG, ADFI, and F/G between allotment strategies at any point in the study or overall. When looking at the coefficient of variation (CV) for pig body weight within each pen, the random or body weight distribution allotment strategies remained relatively consistent over the course of the experiment. Pigs that were grouped by body weight had the lowest within-pen CV at allotment, with CV increasing over the course of the experiment but still being lower than the other two allotment strategies at the conclusion of the trial. For between-pen CV, pigs allotted using the body weight distribution or body weight grouping strategy had the lowest CV on d 0. Pigs allotted using the random strategy had the highest CVs for the entire trial, and pigs allotted using the body weight grouping strategy remained intermediate for the remainder of the trial. The CV of pig body weight within the population was approximately the same for all treatments at allotment. Between d 3 to 21, CV increased the most in pigs allotted using the random strategy, peaking at approximately d 21 and remaining higher than other allotment strategies at the end of the study. The CV for pigs allotted using the body weight distribution and grouping strategies were relatively consistent over the course of the study. Results were used to estimate the replication required with each allotment strategy to obtain significant differences with different percentage responses. The body weight distribution and body weight grouping allotment strategies would require the fewest replications for most response criteria tested. In conclusion, different allotment strategies did not influence average growth performance in any of the 3 phases during the nursery period. However, fewer replications would be required to find similar percentage responses when allotting pigs using the body weight distribution and body weight grouping techniques as compared to the other allotment strategy. When conducting nursery research with pen serving as the experimental unit, the data herein would support that a body weight distribution allotment strategy or body weight grouping strategy would result in the least pen-to-pen variation depending on response.
Keywords: allotment strategies; coefficient of variation; nursery pigs